2016
DOI: 10.1177/0271678x15627657
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the role of toll-like receptor 4 on cell proliferation and inflammation after cerebral ischemia by positron emission tomography

Abstract: The influence of toll-like receptor 4 on neurogenesis and inflammation has been scarcely explored so far by using neuroimaging techniques. For this purpose, we performed magnetic resonance imaging and positron emission tomography with 3 À/À mice after ischemia. These results evidence the versatility of neuroimaging techniques to monitor the role of toll-like receptor 4 after cerebral ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Recently PET has been used to study hypoxia and inflammation in ischemic stroke [ 62 , 63 , 64 , 65 ], to explore the possible relationship between an acute ischemic stroke and Aβ deposition in patients [ 66 ], and to noninvasively image VEGFR expression kinetics to analyze post stroke angiogenesis in rats [ 67 ]. Moreover, 11 C-methionine is the most popular tracer used in PET imaging of brain tumors [ 68 ], and can predict prognosis in gliomas [ 69 ].…”
Section: Positron Emission Tomography (Pet) and Single Photon Emismentioning
confidence: 99%
“…Recently PET has been used to study hypoxia and inflammation in ischemic stroke [ 62 , 63 , 64 , 65 ], to explore the possible relationship between an acute ischemic stroke and Aβ deposition in patients [ 66 ], and to noninvasively image VEGFR expression kinetics to analyze post stroke angiogenesis in rats [ 67 ]. Moreover, 11 C-methionine is the most popular tracer used in PET imaging of brain tumors [ 68 ], and can predict prognosis in gliomas [ 69 ].…”
Section: Positron Emission Tomography (Pet) and Single Photon Emismentioning
confidence: 99%
“…When TLR2 and TLR4 are not activated, MyD88, IL-IR relative kinase (IRAK) combined with MyD88 regulating protein-toll relevant protein. When TLR2 and TLR4 are activated, toll relevant protein separated with MyD88 and IRAK, and then the phosphorylation of IRAK will result in the transfer of NFkB into the nuclear, which further activate the expression of various inflammatory factors [15][16][17][18]. There was research which reported that miR-146a and miR-146b can targeted regulate and control the expression of TLR2 and TLR4 [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the role of the toll-like receptor 4 (TLR4) in the post-ischemic stroke inflammation and neurogenesis was studied using two different radiotracers, 3 0 -[ 18 F]fluorothymidine (FLT) and 1-(2-chlorophenyl)-N-[ 11 C]methyl-N-(1-methyl propyl)-3-isoquinoline carboxamide ([ 11 C]PK11195). 47 The combination of these radiotracers allowed the observation of cell proliferation and inflammation through the translocation protein (TSPO) expression in TLR4 +/+ and TLR4 À/À mice. Additionally, it revealed time-dependent neurogenesis and inhibition of inflammation associated with the lack of TLR4.…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%